Can the Logistics Label Be an Omnichannel Tool? – The Distributor's Perspective - Adam KOLINSKI; Roman DOMANSKI (Communications of International Proceedings, 2021)
The present article draws attention to researchers' niche approach to the subject of omnichannel tools. The authors of this article propose that one of omnichannel tools should be the logistics label with the barcode. Its use is conducive to increasing the operational efficiency of sales and distribution processes, including multi-channel solutions. The aim of the article is to identify and evaluate the type of logistics label standards used by distributors in warehousing and transport processes. In the theoretical part, a systematic review of articles from Scopus and Web of Science databases was used. In the practical part, a questionnaire survey was applied on a sample of 57 enterprises from the TFL (Transport-Forwarding-Logistics) sector in Poland. The literature search did not identify any articles related to the logistics label in the context of the omnichannel concept. This is due to a small total number of articles devoted strictly to the logistics label. The questionnaire survey showed that the use of logistics labels in storage is more common than in transport. In both of these areas, a comparable competitiveness of private labels in relation to standard GS1 labels is observed. The logistics label with the barcode is the primary logistics tool. The omnichannel concept opens further new opportunities to the logistics label to improve trade and distribution processes. In this approach, the logistics label is a tool for standardizing the flow of products and information in the environment of multiple sales and distribution channels.
Keywords: Omni-channel tool; logistics label; warehousing; transport; Transport-Forwarding-Logistics (TFL) sector; Global System One (GS1); standardization; systematic literature review; questionnaire survey